Perception, motivation, and needs of students and lecturers towards Bookcretor-assisted Ethnopedagogy-based e-module in learning Indonesian as a foreign speaker - Ernalida, Ernalida; Sholikhah, Hani Atus; Purnomo, Mulyadi Eko; Nurhayati, Nurhayati; Mayrita, Hastari (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the perceptions, motivations, and needs of both students and lecturers regarding the use of an ethnopedagogy-based module supported by the Book Creator application in teaching Indonesian as a Foreign Language (BIPA). A descriptive quantitative method was employed, involving 210 international BIPA students and 45 lecturers from various universities worldwide. Data were gathered using a Likert-scale questionnaire covering perception, intrinsic and extrinsic motivation, and learning needs, and analyzed through descriptive statistical techniques. Findings revealed that students expressed highly favorable perceptions of the module, with an average score of 4.7. Their intrinsic and extrinsic motivation also scored highly, averaging 4.8 and 4.7 respectively, indicating a strong desire to engage with the module. In terms of needs, students recorded a score of 4.8, highlighting the module’s essential role in their learning process. Lecturers also gave high ratings, with an overall perception score of 4.6 and a module evaluation of 4.7. The study concludes that the module is both relevant and effective, strengthening language acquisition through integration with local cultural contexts. The implication is a clear call for broader adoption and development of similar culture- and technology-integrated modules to enhance the global quality of BIPA instruction.